The Right to Be Forgotten Regulation for Former Convicts in Indonesia - Maria Yohana; Aji Lukman Ibrahim (Law Development Journal, 2025)
This paper discusses the regulation of the right to be forgotten for former prisoners in Indonesia as an effort to support social reintegration and reduce recidivism rates. Based on normative legal research with legislative, comparative, and conceptual approaches, this study examines the regulation of the right to be forgotten in several countries such as the European Union, Japan, and South Korea, which have comprehensively regulated it in personal data protection laws. Meanwhile, in Indonesia, although it has been recognized in Article 26 of the ITE Law, Article 15 of Government Regulation No. 71 of 2019, and Article 8 of the PDP Law, the regulation is still partial, non-operational, and does not specify the requirements and mechanisms for its implementation, especially for former prisoners. Therefore, the author recommends a revision to Article 26 of the ITE Law to change the lawsuit mechanism to a request and add clear, selective, and proportional substantive provisions and exceptions to optimize the granting of the right to be forgotten for former prisoners who meet certain requirements.